Screening of three leguminous crops for drought stress tolerance at germination and seedling growth stage - PANTOLA, SUMAN; VIBHUTI, VIBHUTI; BARGALI, KIRAN; BARGALI, SURENDRA S (The Indian Journal of Agricultural Sciences, 2017)
Responses of three leguminous crops (Glycine max L., Macrotyloma uniflorum L. and Vigna mungo L.) to drought stress imposed at germination and seedling growth stages were investigated in a laboratory experiment. Seeds of selected crops were surface sterilized and placed under five drought stress levels of 0 (control), -5, -10, -15, -20 bar using Mannitol solution. The results showed that with increasing drought stress, germination in all the species was delayed and decreased. The G. max showed maximum germination percentage while M. uniflorum showed minimum germination percentage. Decrease in dry mass of seedlings with increasing drought stress indicated that the stress not only affected germination but also the growth of seedlings. The proper understanding of interactive responses of different crops at different growth stages is a necessity for sustainable crop production under adverse environmental conditions.